The Role of the Pastor in Stewardship of the Church during the Covid-19 Pandemic - Ngesthi, Yonathan Salmon Efrayim; Suparti, Hana; Daliman, Muner; Purwoko, Paulus Sentot (Technium Social Sciences Journal, 2021)
The church is currently in a difficult time to be able to perform all services, as a result of this ongoing pandemic. Shepherds have a fear of pandemics but shepherds are also in their calling to continue to serve. Through descriptive qualitative research methods, it can be concluded that pastors can do this by equipping and understanding about stewardship according to the Bible. Furthermore, in the ministry, bringing the relationship between the Church and Stewardship as a basis for actualizing so as to carry out the duties and Role of the Pastor in Church Stewardship which is currently aimed at stewardship during the COVID-19 pandemic Although the problem of this disease outbreak cannot stop the pastor from carrying out church stewardship services, because the church must continue to be able to adapt and survive in its dependence on God, so that the church can do various ways in accordance with the rules of the government health protocol program which must be strictly adhered to.